The Influence of Work Culture and Individual Characteristics on Employee Performance with Work Effectiveness as an Intervening Variable at the National Land Office of Cianjur Regency - Najmah Fatin; M. Zahari; Sudirman Sudirman (Dinasti International Journal of Digital Business Management, 2026)
This study aims to describe the work habits, individual characteristics, work effectiveness, and performance of employees at the National Land Office of Cianjur Regency. As well as wanting to find out the direct and indirect influence of work culture and individual characteristics on employee performance, both directly and indirectly through work effectiveness. The population in this study is employees of the Cianjur Regency Land Office which totals 53 employees. Saturated sampling was used in this study in determining the sample size, this is usually used for samples that are relatively a little less than 100. This study uses a quantitative approach with a survey method and uses Partial Least Square (PLS) data analysis. The results of the study show that work culture and individual characteristics directly and indirectly through work effectiveness have a positive and significant effect on employee performance, as well as work effectiveness directly has a positive and significant effect on performance performance. This explains that if employees have a good work culture, and are supported by good individual characteristics, it will be able to increase the effectiveness of employee work that supports the achievement of optimal employee performance. In other words, work effectiveness is an important factor that mediates the relationship between work culture and individual characteristics and employee performance